Effects of root exudates of wheat isogenic by Vrn loci lines on growth dynamics, trophic chemotaxis and indole-3-acetic biosynthesis of the specific diazothroph Azospirillum brasilense 410 - Самойлов, А. М.; Жмурко, В. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
Effects of root exudates of near isogenic by Vrn loci soft wheat lines (cultivar Mironovskaya 808) on growth dynamics of diazothrophic bacterium Azospirillum brasilense 410, its trophic chemotaxis to the exudates and indole-3-acetic acid biosynthesis were studied in a nitrogen-free culture medium when the root exudates added. Azospirilla accumulated highest biomass during co-cultivation with the root exudates of seedlings of isogenic by Vrn-D1 and Vrn-A1 lines. In the experiments has no found a difference in trophic chemotaxis to exometabolites of seedlings of these isogenic lines. A treatment of the seedling root exudates of isogenic by Vrn-B1 line and winter cultivar Mironovskaya 808 induced the greatest accumulation of IAA in the culture medium. It is suggested that the shown differences in the azospirilla’ response to the root exudates of seedlings of wheat isogenic lines due to heterogeneity of seeds formed on plants with different Vrn loci states.